Visual acuity impairment in patients with retinitis pigmentosa - Sabbaghi , Hamideh; Daftarian , Narsis; Fakhri , Maryam; Kheiri , Bahareh; Ahmadieh, Hamid (Researcher Bulletin of Medical Sciences, 2022)
Purpose: To determine the visual acuity (VA) impairment in patients with retinitis pigmentosa (RP) in different age groups. Materials and Methods: This descriptive study was extracted from the recorded data in the National Registry for Inherited Retinal Diseases (IRDs) in Iran (IRDReg®). The clinical records of 441 patients with a diagnosis of RP were investigated in the present study. The comprehensive visual and ocular examination with retinal imaging were conducted for all study subjects to ascertain the definite clinical diagnosis of RP. VA was classified based on the presenting VA (PGVA) of the better eye according to the International Classification of Diseases reported by the World Health Organization (WHO). Results: In this study, a total of 441 RP patients with the mean age of 38.66 ± 14.24 years (range, 4 to 74) were included. Generally, the majority of RP patients in the age range of 20 to 40 years had visual impairment (80%; 95% CI, 74.3% to 84.9%). RP patients with younger ages had mild visual impairment (26.3%; 95% CI, 14.4% to 41.7%), while patients with no light perception was only found in older ages (3.4%; 95%CI, 1.4% to 6.8%), (P<0.001). The most frequency of RP patients suffering from visual impairment had disease onset at age ≤20 years (82.0%; 95% CI, 77% to 86.2%), and also severe visual impairment was observed in patients with earlier disease onset (2.6%; 95% CI, 1.2% to 5.1%), (P=0.001). Conclusion: Based on our findings, more disease progression and subsequently visual acuity reduction was observed in RP patients who had older ages and disease onset in younger ages.